Functional modified high-nickel positive electrode composite material and preparation method thereof
By constructing a Si-O-Si three-dimensional mesh structure coating on the surface of high-nickel positive electrode material and grafting fluorine-containing groups, the problem of degradation of cyclic performance of high-nickel positive electrode material is solved, and the long-term operation stability of the material and the improvement of lithium ion transmission efficiency are achieved.
Patent Information
- Application Number
- CN202510120136.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-25
AI Technical Summary
Due to the high nickel content, high nickel positive electrode materials have an exponential increase in the activity of the surface interface and a decrease in circulation performance. Traditional isolation measures cannot effectively solve the sediment problem in the surface interface of the material.
By constructing a Si-O-Si three-dimensional mesh structure coating on the surface of high-nickel positive electrode material, and grafting fluorine-containing groups on its surface to form a fluorine-containing group-rich coating, inhibiting the decomposition of the electrolyte and enhancing the interfacial diffusion ability of lithium ions.
It effectively improves the circulation performance and long-term operation stability of high-nickel positive electrode materials, and promotes lithium ion transmission by forming lithium-rich fluoride with high mechanical strength.
Smart Images

Figure CN119812283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a functionally modified high-nickel positive electrode composite material and a preparation method thereof. Background Art
[0002] With the pursuit of high energy density, the nickel content of ternary cathode materials continues to increase. However, the higher nickel content leads to an exponential increase in the activity of the surface interface, which ultimately causes a rapid decline in cycle performance. Traditional metal oxides can only isolate electrolyte corrosion, while the deposits on the surface interface of the material will continue to increase.
[0003] Recently, the fluorine element has been widely used in material modification schemes. For example, patent CN112186190A discloses a high-voltage lithium-ion battery. Among them, the positive electrode adopts a high-voltage fluorinated positive electrode material, and the electrolyte is composed of a cosolvent of a fluorinated ether and an additive composed of a fluorinated carbonate and a boron-containing substance. The high-voltage positive electrode material is initially treated with fluorination to establish a fluorine-containing interface layer, and then the interface layer is modified and consolidated by a fluorinated electrolyte, thereby effectively improving the high-voltage cycle performance of the lithium-ion battery. Patent CN118738560A discloses a fluorocarbon electrolyte additive, which can assist in the formation of a fluorine-rich CEI film on the surface of the material through a fluorocarbon chain. It can not only improve the ionic conductivity, but also inhibit the occurrence of interfacial side reactions. It can be seen that fluorine-containing substances, whether as a modified material for the positive electrode material or as an additive for the electrolyte, are of great help in improving the various performances of the positive electrode material. However, at present, fluorine-modified materials are only limited to fluorine doping or fluoride coating, and fail to give full play to the advantages of high-nickel positive electrode materials. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a functional modified high-nickel positive electrode composite material, the preparation method comprising the following steps:
[0005] (1) dissolving tetraethyl orthosilicate in a mixed solution of ethanol and ammonia water, then adding a high-nickel positive electrode material and stirring for a period of time;
[0006] Among them, the high nickel positive electrode material is: LiNi 1-x-y Co x Mn y O2(x≤0.1,y≤0.1).
[0007] The molar ratio of ethanol to ammonia water is 10-20:1.
[0008] The concentration of ethyl orthosilicate is: 0.005~0.5g / ml.
[0009] The mass ratio of ethyl orthosilicate to high nickel positive electrode material is 0.01-0.5:1.
[0010] Stirring time: 0.5~10h.
[0011] (2) Dispersing the fluorine-containing silane in ethanol, then adding it to the solution of step (1), stirring for a period of time, and then evaporating the solvent to obtain a composite material.
[0012] Wherein, the fluorine-containing silane is: 1H,1H,2H,2H-perfluorodecyltrichlorosilane PFDTS, 3,3,3-trifluoropropyltrimethoxysilane TFTMS or trifluoromethyltrimethylsilane TFMTMS.
[0013] The mass ratio of fluorinated silane to tetraethyl orthosilicate is 0.005-0.02:1.
[0014] The stirring temperature is: 60-70°C, and the stirring time is: 0.5-10h.
[0015] The volatilization temperature is: 60~100℃, and the volatilization time is: 6~12h.
[0016] The present invention preferentially constructs a three-dimensional network structure coating of Si-O-Si on the surface of a high-nickel positive electrode material by hydrolysis and polycondensation of ethyl orthosilicate. Fluorine-containing silane is subsequently added to graft the fluorine-containing groups therein onto the three-dimensional network structure coating of Si-O-Si, so that the outer side of the coating is rich in fluorine-containing groups. The fluorine-containing groups on the outer side of the coating form a CEI film containing LiF by combining with lithium ions during the battery cycle, inhibiting the decomposition of the electrolyte and enhancing the interfacial diffusion capacity of lithium ions, which is of great help to the long-term operation of the battery.
[0017] The beneficial effects of the present invention are:
[0018] The present invention uses a simple solution reaction technology to utilize the hydroxyl groups on the surface of the high-nickel ternary material to react and chemically bond with ethyl orthosilicate, first forming a three-dimensional network structure coating on the surface of the material. Then, reactive silane is added to graft the fluorine-containing groups onto the coating surface. The fluorine-containing groups on the coating surface are conducive to forming lithium-rich fluorides with high mechanical strength during the battery cycle, accelerating lithium ion transmission. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the composite positive electrode material provided in Example 1 of the present invention;
[0020] Figure 2 This is a SEM image of the base material provided in Comparative Example 1 of the present invention;
[0021] Figure 3 This is a cycle performance diagram of the high nickel positive electrode material prepared in Example 1 of the present invention and Comparative Example 1 at 0.5C. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0023] Example 1
[0024] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 58 ml of ammonia water. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0025] (2) 0.0015 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0026] Example 2
[0027] (1) Dissolve 0.015 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 58 ml of aqueous ammonia. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0028] (2) 0.0015 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0029] Example 3
[0030] (1) Dissolve 0.06 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 58 ml of ammonia water. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0031] (2) 0.0015 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0032] Example 4
[0033] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 58 ml of ammonia water. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0034] (2) 0.001 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65°C for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70°C for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0035] Example 5
[0036] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 58 ml of ammonia water. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0037] (2) 0.002 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65°C for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70°C for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0038] Example 6
[0039] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 20 ml of aqueous ammonia. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0040] (2) 0.0015 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0041] Example 7
[0042] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 100 ml of ammonia water. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0043] (2) 0.0015 g of PFDTS was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0044] Example 8
[0045] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 60 ml of aqueous ammonia. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0046] (2) 0.0015 g of 3,3,3-trifluoropropyltrimethoxysilane (TFTMS) was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. and dried for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0047] Example 9
[0048] (1) Dissolve 0.03 g of tetraethyl orthosilicate in a mixed solution of 100 ml of ethanol and 60 ml of aqueous ammonia. After stirring for 30 min, add 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material and stirred again for 6 hours to obtain a mixed solution A.
[0049] (2) 0.0015 g of trifluoromethyltrimethylsilane (TFMTMS) was dispersed in 10 ml of ethanol to form solution B, and then the mixed solution B was added dropwise to the mixed solution A, and stirred at 65° C. for 6 h to obtain a mixed solution C. Finally, the mixed solution C was placed in a vacuum drying oven at 70° C. for 12 h to obtain a high-nickel cathode material modified with a functional coating.
[0050] Comparative Example 1
[0051] LiNi without any treatment 0.8 Co 0.1 Mn 0.1 The O2 high nickel positive electrode material is comparative example 1.
[0052] Comparative Example 2
[0053] 0.03 g of tetraethyl orthosilicate was dissolved in a mixed solution of 100 ml of ethanol and 58 ml of ammonia water. After stirring for 30 min, 2 g of LiNi 0.8 Co 0.1 Mn 0.1 O2 high nickel positive electrode material, and stirred again for 6 hours to obtain a mixed solution. The mixed solution was dried at 70°C for 12 hours to obtain a high nickel positive electrode material modified with only SiO2.
[0054] The composite positive electrode material prepared in Example 1 and the base material of Comparative Example 1 were subjected to SEM tests respectively. Figure 1-2 As shown, the surface of the composite positive electrode material prepared in Example 1 is relatively rough, while the surface of the base material prepared in Comparative Example 1 is very smooth, indicating that the surface of the high-nickel positive electrode material is covered with a layer of functional coating.
[0055] Figure 3 The cycle performance diagram of Example 1 and Comparative Example 1 at 0.5C is shown. It can be found that the capacity retention rate of Example 1 after 100 cycles is 97%, while that of Comparative Example 1 is only 92%, indicating that the functional coating effectively improves the cycle performance of the high-nickel positive electrode material.
[0056] The composite positive electrode materials corresponding to Examples 1-9 and the matrix materials corresponding to Comparative Examples 1 and 2 were used as positive electrode active materials to prepare positive electrode sheets. Next, button cells were assembled with lithium sheets as negative electrodes, and then the electrochemical performance of all batteries was tested in the voltage range of 2.75-4.3V. The test results are shown in Table 1:
[0057] Table 1
[0058]
[0059] In Table 1, it can be seen from Comparative Example 1 and Comparative Example 2 that constructing a functional coating containing O-Si-O on the surface of the material can effectively improve the first effect and cycle performance of the material. It can be seen from Comparative Example 2 and Example 1 that grafting fluorine-containing functional groups on the surface of the SiO2 coating slightly reduces the first effect, but improves the cycle stability. It can be seen from Example 1, Example 2, and Example 3 that an appropriate SiO2 coating thickness can improve the interface stability of the material. It can be seen from Example 1, Example 4 and Example 5 that a small amount of fluorine-containing groups can improve the first effect and cycle stability, but when the fluorine-containing groups increase, a large amount of active lithium is consumed to form a CEI film, which reduces the first sale. It can be seen from Example 1, Example 6 and Example 7 that adding too little ammonia water will affect the rate of hydrolysis and condensation of ethyl orthosilicate, which may affect the incompleteness of the coating on the surface of the high-nickel positive electrode material, but too much ammonia water will accelerate the hydrolysis and condensation rate of ethyl orthosilicate, causing it to agglomerate and unable to wrap the high-nickel positive electrode material. It can be seen from Example 1, Example 8 and Example 9 that different fluorine-containing silanes can assist in forming fluorine-containing groups on the coating surface. It can be seen from Example 1 and Comparative Example 1 that the material can be effectively protected by functional coating modification, and the lithium ion diffusion capacity can be improved by constructing an inorganic CEI film of LiF.
[0060] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0061] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a functional modified high-nickel cathode composite material, characterized in that: The preparation method steps are as follows: (1) dissolving tetraethyl orthosilicate in a mixed solution of ethanol and ammonia water, and then adding a high-nickel positive electrode material and stirring; (2) Dispersing the fluorine-containing silane in ethanol, then adding it to the solution of step (1), stirring, and then evaporating the solvent to obtain a composite material.
2. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The high nickel positive electrode material in step (1) is: LiNi 1-x-y Co x Mn y O2, where x≤0.1, y≤0.
1.
3. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The molar ratio of ethanol to ammonia water in step (1) is 10-20:1, and the stirring time is 0.5-10 hours.
4. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The concentration of the tetraethyl orthosilicate in step (1) is 0.005-0.5 g / ml.
5. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The mass ratio of the tetraethyl orthosilicate to the high-nickel positive electrode material in step (1) is 0.01 to 0.5:
1.
6. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The fluorine-containing silane in step (2) is: 1H,1H,2H,2H-perfluorodecyltrichlorosilane PFDTS, 3,3,3-trifluoropropyltrimethoxysilane TFTMS or trifluoromethyltrimethylsilane TFMTMS.
7. The method for preparing the functional modified high nickel cathode composite material according to claim 1, characterized in that: The mass ratio of the fluorine-containing silane to tetraethyl orthosilicate in step (2) is 0.005-0.02:
1.
8. The method for preparing the functional modified high-nickel cathode composite material according to claim 1, characterized in that: The stirring temperature in step (2) is 60-70° C., and the stirring time is 0.5-10 h.
9. The method for preparing the functional modified high nickel cathode composite material according to claim 1, characterized in that: The evaporation temperature of the solvent in step (2) is 60 to 100° C., and the evaporation time is 6 to 12 hours.
10. A functionally modified high-nickel positive electrode composite material prepared according to the method of claim 1.
Citation Information
Patent Citations
Fluorosilane-coated composite positive electrode material as well as preparation method and application thereof
CN112421039A
Ternary positive electrode material and preparation method and application thereof
CN112670482A
Preparation method of functional polymer coated high-nickel positive electrode material
CN116565164A